REDUCING THE IMPACT ON HARVESTING THROUGH ARTIFICIAL INTELLIGENCE TECHNOLOGIES - Davron Shamsievich Ziyadullaev; Daniil Vyacheslavovich Shunkevich; Yusuf Yakhshiboevich Muhammadiev; Laziz Azimzhonovich Orakov (Galaxy International Interdisciplinary Research Journal, 2022)
The article discusses how artificial intelligence technology can reduce the risk involved in harvesting crops. According to experts, most of them, especially in all private property, market, manufacturing, family, education, public and legal institutions, will undergo radical changes.